2014
DOI: 10.1111/ijac.12305
|View full text |Cite
|
Sign up to set email alerts
|

Development of Silicon Nitride‐Based Ceramic Radomes — A Review

Abstract: Radome is an aerodynamic structural part attached to the fore‐end of a missile. It transmits electromagnetic signals with minimum attenuation and also protects radar communication system, and thus, the radomes are made of ceramics as they have desirable properties required by the radomes. The flexural strength, dielectric constant, and loss tangent values of various ceramic materials used in the development of radomes are important in the selection of radome materials. Different nose cone shapes of missile rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 96 publications
(81 reference statements)
0
28
0
Order By: Relevance
“…Although several alternatives of structural ceramics have been proposed, silicon nitride (Si 3 N 4 )-based ceramics remain competitive due to their superior properties, involving high strength and hardness at elevated temperatures, high resistance to oxidation and chemical attack, low coefficient of tribological friction and thermal expansion, and low dielectric permittivity, etc. [1][2][3][4][5][6][7][8][9][10]. As important multifunctional materials, Si 3 N 4 ceramics have found wide range of successful application towards gas turbine engine components [10][11][12][13][14], cutting tools [11,15], radomes [2], and even integrated circuit [16,17], optical devices [18,19], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several alternatives of structural ceramics have been proposed, silicon nitride (Si 3 N 4 )-based ceramics remain competitive due to their superior properties, involving high strength and hardness at elevated temperatures, high resistance to oxidation and chemical attack, low coefficient of tribological friction and thermal expansion, and low dielectric permittivity, etc. [1][2][3][4][5][6][7][8][9][10]. As important multifunctional materials, Si 3 N 4 ceramics have found wide range of successful application towards gas turbine engine components [10][11][12][13][14], cutting tools [11,15], radomes [2], and even integrated circuit [16,17], optical devices [18,19], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective approaches to ensure rapid consolidation and high mechanical performance of Si 3 N 4 -based ceramics are actively being explored, including gas pressure sintering (GPS) [11], hot-pressing sintering (HPS) [20][21][22][23][24][25][26], hot isostatic pressing sintering (HIP) [27], spark plasma sintering (SPS) [26,28,29], and microwave sintering [1,30], etc. However, considering the requirement of high gas pressures for gas pressure sintering and extra current devices for SPS with a significantly higher furnace costs, HPS allows the dense and complex-shaped parts with medium cost [2]. Previous considerable efforts have demonstrated that fully dense Si 3 N 4 ceramics with superior strength could be achieved through liquid phase sintering by (d 50 = 5 µm, purity > 98%) were kindly provided by Forsman Scientific Co., Ltd., Beijing, China.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of alternatives of structural ceramics have been proposed, silicon nitride (Si3N4)-based ceramics remain competitive due to their superior properties, involving high strength and hardness at elevated temperatures, high resistance to oxidation and chemical attack, low coefficient of tribological friction and thermal expansion, and low dielectric permittivity, etc. [1][2][3][4][5][6][7][8][9] . As important multifunctional materials, Si3N4 ceramics have found wide range of successful application towards gas turbine engine components [10][11][12][13] , cutting tools [10,14] , radomes [2] , and even integrated circuit [15,16] , optical devices [17,18] , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nitride ceramics have attracted considerable attention in recent decades due to their high strength retention at room and elevated temperatures, high thermal‐shock resistance, high‐temperature stability, hardness, excellent erosion resistance, and corrosion resistance . Owing to these characteristics, silicon nitride ceramics are widely used in various industries, such as automotive, aerospace, machinery, etc …”
Section: Introductionmentioning
confidence: 99%